Orbital and physical parameters of eclipsing binaries from the ASAS catalogue – IX. Spotted pairs with red giants. Issue 2 (17th June 2016) - Ratajczak, M.; Hełminiak, K. G.; Konacki, M.; Smith, A. M. S.; Kozłowski, S. K.; Espinoza, N.; Jordán, A.; Brahm, R.; Hempel, M.; Anderson, D. R.; Hellier, C.
Abstract: We present spectroscopic and photometric solutions for three spotted systems with red giant components. Absolute physical and orbital parameters for these double-lined detached eclipsing binary stars are presented for the first time. These were derived from the V -, and I -band ASAS and WASP photometry, and new radial velocities calculated from high quality optical spectra we obtained with a wide range of spectrographs and using the two-dimensional cross-correlation technique (TODCOR). All of the investigated systems (ASAS J184949-1518.7, BQ Aqr, and V1207 Cen) show the differential evolutionary phase of their components consisting of a main-sequence star or a subgiant and a red giant, and thus constitute very informative objects in terms of testing stellar evolution models. Additionally, the systems show significant chromospheric activity of both components. They can be also classified as classical RS CVn-type stars. Besides the standard analysis of radial velocities and photometry, we applied spectral disentangling to obtain separate spectra for both components of each analysed system which allowed for a more detailed spectroscopic study. We also compared the properties of red giant stars in binaries that show spots, with those that do not, and found that the activity phenomenon is substantially suppressed for stars with Rossby number higher than ∼1 and radii larger than ∼20 R⊙ .